Astronauta : la vida en el espacio - Hayden, Kate.; Dennis, Peter; Foresman, Scott (New York : DK, 2006)
Describes the various steps necessary for an astronaut to prepare for a flight into space and follows astronaut Linda Gardner as she trains for her space shuttle mission.
Includes index.
DK Readers
Keywords: Life support systems (Space environment) -- Juvenile literature; Astronauts -- Juvenile literature; Spanish language materials -- Juvenile literature; Astronautas -- Literatura juvenil; Sistemas mantenedores de vida (Ambiente espacial) -- Literatura juvenil